Effect of sacubitril–valsartan on left ventricular remodeling in patients with acute myocardial infarction after primary percutaneous coronary intervention: a systematic review and meta-analysis - Liu, Yiheng; Sun, Yue; Dai, Weiran (Frontiers in Pharmacology, 2024)
Background Sacubitril–valsartan has been widely reported for reducing the risk of cardiovascular death and improving left ventricular remodeling in patients with heart failure (HF). However, the effect of sacubitril–valsartan in patients with acute myocardial infarction (AMI) remains controversial. Therefore, we conducted this meta-analysis to investigate whether sacubitril–valsartan could reverse left ventricular remodeling and reduce cardiovascular adverse events in AMI patients after primary percutaneous coronary intervention (PPCI). Materials and methods Two researchers independently retrieved the relevant literature from PubMed, Embase, The Cochrane Library, China National Knowledge Infrastructure (CNKI), and the Wanfang database. The retrieval time was limited from inception to 1 June 2023. Randomized controlled trials (RCTs) meeting the inclusion criteria were included and analyzed. Results In total, 21 RCTs involving 2442 AMI patients who underwent PPCI for revascularization were included in this meta-analysis. The meta-analysis showed that compared with the angiotensin-converting enzyme inhibitors (ACEI)/angiotensin receptor blockers (ARB), sacubitril–valsartan treatment in AMI patients after PPCI significantly reduced left ventricular end-diastolic dimension (LVEDD) (weighted mean difference (WMD) −3.11, 95%CI: −4.05∼−2.16, p < 0.001), left ventricular end-diastolic volume (LVEDV) (WMD −7.76, 95%CI: −12.24∼−3.27, p = 0.001), left ventricular end-systolic volume (LVESV) (WMD −6.80, 95%CI: −9.45∼−4.15, p < 0.001) and left ventricular end-systolic dimension (LVESD) (WMD −2.53, 95%CI: −5.30–0.24, p < 0.001). Subgroup analysis according to the dose of sacubitril–valsartan yielded a similar result. Meanwhile, PPCI patients using sacubitril–valsartan therapy showed lower risk of major adverse cardiac events (MACE) (OR = 0.36, 95%CI: 0.28–0.46, p < 0.001), myocardial reinfarction (OR = 0.54, 95%CI: 0.30–0.98, p = 0.041) and HF (OR = 0.35, 95%CI: 0.26–0.47, p < 0.001) without increasing the risk of renal insufficiency, hyperkalemia, or symptomatic hypotension. At the same time, the change of LV ejection fraction (LVEF) (WMD 3.91, 95%CI: 3.41–4.41, p < 0.001), 6 min walk test (6MWT) (WMD 43.56, 95%CI: 29.37–57.76, p < 0.001) and NT-proBNP level (WMD −130.27, 95%CI: −159.14∼−101.40, p < 0.001) were statistically significant. Conclusion In conclusion, our meta-analysis indicates that compared with ACEI/ARB, sacubitril–valsartan may be superior to reverse left ventricular remodeling, improve cardiac function, and effectively reduce the risk of MACE, myocardial reinfarction, and HF in AMI patients after PPCI during follow-up without increasing the risk of adverse reactions including renal insufficiency, hyperkalemia, and symptomatic hypotension.